2010
DOI: 10.1200/jco.2010.29.1351
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Overall Treatment Time on Survival and Local Control in Patients With Anal Cancer: A Pooled Data Analysis of Radiation Therapy Oncology Group Trials 87-04 and 98-11

Abstract: A B S T R A C T PurposeTo determine whether increased duration of radiation therapy (RT) and overall treatment (RX) time has a detrimental effect in anal cancer. Patients and MethodsData from Radiation Therapy Oncology Group (RTOG) 87-04 and RTOG 98-11 trials were combined to form three treatment groups: RT/fluorouracil (FU)/mitomycin (n ϭ 472), RT/FU/ cisplatin (n ϭ 320), and RT/FU (n ϭ 145). Cox proportional hazards models were used with the following variables: RT duration, RT intensity, RX duration, treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(60 citation statements)
references
References 35 publications
5
55
0
Order By: Relevance
“…Time to completion of therapy has been shown to have an impact on survival in patients undergoing radiation therapy, yet this relationship is less well-defined in patients receiving chemotherapy (13,14). Though no studies have been performed in patients with EOC, decreased survival has been documented in breast cancer patients who experience delays and dose reductions in chemotherapeutic regimens [15-18].…”
Section: Discussionmentioning
confidence: 99%
“…Time to completion of therapy has been shown to have an impact on survival in patients undergoing radiation therapy, yet this relationship is less well-defined in patients receiving chemotherapy (13,14). Though no studies have been performed in patients with EOC, decreased survival has been documented in breast cancer patients who experience delays and dose reductions in chemotherapeutic regimens [15-18].…”
Section: Discussionmentioning
confidence: 99%
“…In cervical and anal cancer the duration of chemotherapy was reported to have a decisive effect on the patients’ survival [7, 8]. In EOC data on the association between duration of chemotherapy and survival outcome are partially inconsistent.…”
Section: Introductionmentioning
confidence: 99%
“…All eventually had a complete clinical response and currently have no evidence of disease. Some studies have not shown an association between treatment breaks with worse clinical outcomes, including a pooled data analysis of RTOG 87-04 and 98-11 [30,31]. Although the effect of a treatment break is unclear, an uninterrupted treatment course should be delivered if possible.…”
Section: Discussionmentioning
confidence: 99%